If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x+6)/7=(1-x)/5
We move all terms to the left:
(3x+6)/7-((1-x)/5)=0
We add all the numbers together, and all the variables
(3x+6)/7-((-1x+1)/5)=0
We calculate fractions
3x/()+(-((-1x+1)*7)/()=0
We calculate terms in parentheses: +(-((-1x+1)*7)/(), so:We get rid of parentheses
-((-1x+1)*7)/(
We multiply all the terms by the denominator
-((-1x+1)*7)
We calculate terms in parentheses: -((-1x+1)*7), so:We get rid of parentheses
(-1x+1)*7
We multiply parentheses
-7x+7
Back to the equation:
-(-7x+7)
7x-7
Back to the equation:
+(7x-7)
3x/()+7x-7=0
We multiply all the terms by the denominator
3x+7x*()-7*()=0
We add all the numbers together, and all the variables
3x+7x*()=0
| 45=5(y-2) | | 15=k*6 | | -76+63x=9(4+7x)+6 | | 2s+10=2 | | 18-8n=5+5(-4n-7) | | 10w-5=5 | | 2x(3-x^2)=6x+54 | | 3=3(1+t) | | x-10-3=-7 | | -12-5(6+-2m)=18 | | 7y=81−17.3 | | 8(x-5)+5x=12 | | x-10-3=7 | | |x-10|-3=7 | | -5(v+4)=-2v-2 | | 5x/3-6+2(x+2)=2(x+4) | | 5y-18=20 | | 2(x-5)=4x-(10-2x) | | -50=-4-6x | | 6(c+6)=-30 | | 9x+2x+7=3x-7 | | 6y=y+70 | | 1,840=23(p+15) | | 3x+5x=-10 | | v+15=6v | | -6(8+3x)=-138 | | 4=6-2d | | 26+3g=32 | | -2x+4(-9-6)=-10-7(2x-10) | | p-4=-14 | | 2x+2x+9+90=180 | | -7(8k-7)+2(1-3k)=-11 |